2004
DOI: 10.1115/1.1748294
|View full text |Cite
|
Sign up to set email alerts
|

Impermeable Crack and Permeable Crack Assumptions, Which One is More Realistic?

Abstract: This paper investigates the applicability and effect of the crack-free electrical boundary conditions in piezoelectric fracture. By treating flaws in a medium as notches with a finite width, the results from different electrical boundary condition assumptions on the crack faces are compared. It is found that the electrically impermeable boundary is a reasonable one for engineering problems. Unless the flaw interior is filled with conductive media, the permeable crack assumption may not be directly applied to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(56 citation statements)
references
References 17 publications
1
55
0
Order By: Relevance
“…The impermeable crack and permeable crack models have been used in previous studies on the crack problems. Recently, Wang and Mai [13] showed that the electrically impermeable boundary is a reasonable one for engineering problems. Thus, we use the impermeable crack surface condition in this paper.…”
Section: Asymptotic Problemmentioning
confidence: 99%
“…The impermeable crack and permeable crack models have been used in previous studies on the crack problems. Recently, Wang and Mai [13] showed that the electrically impermeable boundary is a reasonable one for engineering problems. Thus, we use the impermeable crack surface condition in this paper.…”
Section: Asymptotic Problemmentioning
confidence: 99%
“…Some researchers [8] believe that anti-plane cracks are electrically permeable, because crack surfaces are in contact when loaded by anti-plane static shear. However, some other researchers [9] argue that both in-plane and anti-plane cracks are Fig. 1 An interface crack in a graded piezoelectric structure with finite dimension electrically impermeable, because a flaw in engineering materials is always a notch of finite thickness rather than a slit crack.…”
Section: Introductionmentioning
confidence: 97%
“…They presented the solutions in the series form of the displacement function and the electric potential function. For the assumption of the electric boundary condition, Wang and Mai [14] derived the solutions of the field intensity factors at the crack tip under the impermeable crack assumption and the permeable crack assumption, respectively. The results showed that, unless the crack was extremely flat or the flaw interior was filled with conductive media, the electrically impermeable boundary was a reasonable one.…”
Section: Introductionmentioning
confidence: 99%